2022
DOI: 10.3389/fmars.2022.902674
|View full text |Cite
|
Sign up to set email alerts
|

Gelatinous Carbon Impacts Benthic Megafaunal Communities in a Continental Margin

Abstract: Post-collapse of seasonal blooms of gelatinous zooplankton (Cnidaria, Ctenophora, and Thaliacea) sinking carcasses transports labile carbon (jelly-C) to benthic continental margins and the deep sea. In recent decades, bloom frequency and intensity have increased globally; however, how sinking jelly-C affects benthic communities is poorly known. Further, as climate change and other anthropogenic impacts may increase gelatinous blooms in the future, understanding the contributions and impacts of jelly-C upon ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Significantly higher pyrosome densities in disturbed areas than those observed elsewhere during the same survey days confirmed that seafloor morphology was the main reason for differences in pyrosome density. Such accumulations of pyrosomes have also been observed along the sides of pipelines and in depressions off West Africa (Lebrato and Jones, 2009;Lebrato et al, 2022) with salps also having been observed to accumulate in hollows and furrows on the NW Atlantic slope (Cacchione et al, 1978). In order to analyze pyrosome accumulation in disturbed seafloor areas we here pooled undisturbed seafloor areas that included areas with and without nodules.…”
Section: Seafloor Disturbance and Accumulation Of Detritusmentioning
confidence: 94%
“…Significantly higher pyrosome densities in disturbed areas than those observed elsewhere during the same survey days confirmed that seafloor morphology was the main reason for differences in pyrosome density. Such accumulations of pyrosomes have also been observed along the sides of pipelines and in depressions off West Africa (Lebrato and Jones, 2009;Lebrato et al, 2022) with salps also having been observed to accumulate in hollows and furrows on the NW Atlantic slope (Cacchione et al, 1978). In order to analyze pyrosome accumulation in disturbed seafloor areas we here pooled undisturbed seafloor areas that included areas with and without nodules.…”
Section: Seafloor Disturbance and Accumulation Of Detritusmentioning
confidence: 94%